Synthesis and optimization of 4, 5, 6, 7-tetrahydrooxazolo[4, 5-c]pyridines as potent and orally-active metabotropic glutamate receptor 5 negative allosteric modulators. Issue 18 (15th September 2017) - Hirose, Wataru; Kato, Yoshihiro; Natsutani, Itaru; Takata, Makoto; Kitaichi, Maiko; Imai, Satoki; Hayashi, Shun; Arai, Yukiyo; Hoshino, Kohei; Yoshida, Kohzo
Graphical abstract: Abstract: We describe here the design, synthesis and characterization of a series of 4, 5, 6, 7-tetrahydrooxazolo[4, 5- c ]pyridines as metabotropic glutamate receptor (mGluR) 5 negative allosteric modulators (NAMs). Optimization of the substituents led to the identification of several compounds with good pharmacokinetic profiles, including long half life and high oral bioavailability, in both rats and monkeys. The receptor occupancy test in the rat cortex revealed favorable brain penetration of these compounds. The reprsentative compound13 produced oral antidepressant-like effect in the rat forced swimming test (MED: 0.3 mg/kg, q.d.).